The modulation of 9-Chloro-9-Phosphaalkenylchloro-9-Germafluorene reactivity through organolithium reagents. (1st December 2021) - Buta, Lavinia; Septelean, Raluca; Soran, Albert; Aghion, Iulia-Andreea; Moraru, Ionut-Tudor; Nemes, Gabriela
Graphical abstract: The reactivity of 9-chloro-9-phosphaalkenylchloro-9-germafluorene towards organolithium reagents is influenced by their nature. Reagents such as methyllithium and n -butyllithium afford alkylated species of phosphaalkenylchloro-germafluorene at the Ge-Cl unit while the reactions of bulkier sec -butyllithium and tert -butyllithium undergo with the formation of symmetrical and unsymmetrical dimers through involvement of the PC and/or Ge-C moieties. Abstract: The reactivity of 9-chloro-9-phosphaalkenylchloro-9-germafluorene stabilized by the introduction of the germanium atom into a fluorenyl system, was tested in reaction with lithium derivatives as methyllithium, normal -, sec - and tert -butyllithium. The reactions underwent, depending on the used organolithium derivative, either with the alkylation of the germanium atom or through a lithiation of the carbon atom of the phosphaalkenyl unit, and the successive formation of a carbanion through elimination of LiCl followed by the dimerization of this intermediate species.